Effectiveness of Using Heyzine Flipbook Maker-based E-Modules through Problem-Based Learning Model - Revita Yuni; Silaban, Putri Sari MJ; Thohiri, Roza; Lubis, Putri Kemala Dewi (Journal of Psychology and Instruction, 2025)
One limitation of this research is that the student teaching module lacks a problem-based approach, has an unappealing appearance, and is infrequently undertaken by students due to its substantial workload. Furthermore, the instructional module has not succeeded in enhancing students' proficiency in higher-order cognitive abilities. The objective of this research is to evaluate the effectiveness of integrating e-modules developed using the Heyzine flipbook creator into a problem-based learning approach within the Economics of Education course. The study was conducted as part of the Economic Education Study Programme at the Faculty of Education, State University of Medan. The research population comprised 77 students from the Education Research Programme, divided into an experimental class of 37 students and a control class of 40 students. The present study employs a quasi-experimental approach to investigate the efficacy of an experimental intervention. The objective of the data analysis is to assess the viability and applicability of the e-module after it is integrated into the learning process. This will enable an evaluation of the efficacy of e-modules in supporting student learning. The findings revealed that the students in the experimental class demonstrated an average level of learning completeness of 79%, while those in the control class exhibited an average of 73%. Consequently, it can be concluded that the acquisition of knowledge by the experimental class students through the utilisation of e-modules based on Heyzine Flipbook Maker, within a problem-based learning framework, was effective.